Analysis of accidents in construction in 2015-2017 - Smolarz, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Worldwide, construction is a branch of the economy characterised by a high level of employee safety risks and a high accident rate. In Poland, over the last 20 years, the number of victims and the frequency of accidents in the construction industry have shown a decreasing tendency, but they are subject to large fluctuations. Current accident reporting methods focused on rigidly classified circumstances and root causes do not facilitate drawing general conclusions for the purpose of prediction.
Keywords: construction; accidents at work; fall from a height; prevention; budownictwo; wypadki przy pracy; upadki z wysokości; zapobieganie